Identifying Historical Centers of Cities and Developing Design Code Rules for Them (In the case of Samarkand and Bukhara) - Jurat Tajibaev (Genius Journals, 2022)
This article describes the development of design code rules for historical cities, the analysis of problems related to the design code elements of Bukhara and Samarkand, the analytical processes and scientific views of determining the historical area of the city. Sections of design code rules are discussed.
Keywords: Design-code rules; historical city framework; plasma; design-code elements